Inventory System PT Azzkiyya Using Microsoft Visual Basic 6.0 - Nunung Komariah; Jalinas SKom, MM (Jurnal Sistem Informasi, 2005)
Inventory system is one of the transaction processing system that are important to the operation of the company organization. Because the company will not be able to meet the needs of its customers if it does not have an adequate inventory. recording data related to inventory and shipping data reporting and data entry and inventory expenses.